HOW TO CONSIDER AND AVOID POTENTIAL SOCIAL MEDIA ATTACKS: CYBER SECURITY AGAINST CYBERCRIME (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
Information and information systems are developing in today's modern world. At the same time, this popularization caused the emergence of a new type of crime, namely cybercrime. This, in turn, ensures the protection of the system and its information. This article highlights the importance of cyber security in the digital economy of countries and the concepts of cybercrime that have created it.